Pengaruh Harga Dan Promosi Terhadap Keputusan Pembelian J.CO Donut Dan Coffee Di Centre Point Medan - Pardosi, Fitri Apriani; Siagian, Nalom; Sinaga, Kepler (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2024)
J.CO Donut and Coffee is one of the most successful brands in meeting customer demand in the Indonesian donut and coffee industry. J.CO has grown rapidly since its inception in 2005, emphasizing unique product flavors, high quality, and modern and comfortable store designs. With a concept that combines urban and modern lifestyles, this donut brand has succeeded in attracting customers from various circles. Research Method : Shows that Price (X1) has a positive and significant effect on Purchasing Decisions (Y), Promotion (X2) has a positive and significant effect on Purchasing Decisions (Y). While Price (X1) and Promotion (X2) simultaneously have a significant effect on Purchasing Decisions (Y). Conclusion : The results of this study can be concluded that Price (X1) has a positive and significant effect on Purchasing Decisions (Y), Promotion (X2) has a positive and significant effect on Purchasing Decisions (Y), while Price (X1) and Promotion (X2) simultaneously have a significant effect on Purchasing Decisions (Y).